Bio-hybrid photoconverter by covalent functionalization of the photosynthetic reaction center of Rhodobacter sphaeroides with fluorescein isothiocyanate. Issue 1722 (16th June 2015) - Tangorra, Rocco Roberto; Antonucci, Alessandra; Milano, Francesco; la Gatta, Simona; Operamolla, Alessandra; Ragni, Roberta; Agostiano, Angela; Trotta, Massimo; Farinola, Gianluca M.
ABSTRACT: Organic biological hybrid systems, accessible by covalent functionalization of photosynthetic proteins with molecular antennas, represent a promising novelty to enhance natural photosynthesis. In this paper, we present the successful bioconjugation of a commercial fluorophore, fluorescein isothiocyanate (FITC), to the photosynthetic reaction center RC from the bacterium Rhodobacter sphaeroides strain R26. The resulting hybrid outperforms the pristine protein in hole-electron couple generation yield, exclusively at wavelengths where the fluorophore absorbs while the protein does not.